Effect of Clenbuterol on Tracheal Mucociliary Transport in Horses Undergoing Simulated Long‐Distance Transportation. (28th August 2013) - Norton, J.L.; Jackson, K.; Chen, J.W.; Boston, R.; Nolen‐Walston, R.D.
<x xml:space="preserve">Abstract</x> Background Pneumonia is observed in horses after long‐distance transportation in association with confinement of head position leading to reduction in tracheal mucociliary clearance rate (TMCR). Hypothesis/Objectives Clenbuterol, a beta‐2 agonist shown to increase TMCR in the horse, will ameliorate the effects of a fixed elevated head position on large airway contamination and inflammation in a model of long‐distance transportation model. Animals Six adult horses. Methods A cross‐over designed prospective study. Horses were maintained with a fixed elevated head position for 48 hours to simulate long‐distance transport, and treated with clenbuterol (0.8 μg/kg PO q12h) or a placebo starting 12 hours before simulated transportation. TMCR was measured using a charcoal clearance technique. Data were collected at baseline and 48 hours, and included TMCR, tracheal wash cytology and quantitative culture, rectal temperature, CBC, fibrinogen, and serum TNFα, IL‐10, and IL‐2 levels. There was a 18–21 day washout between study arms, and data were analyzed using regression analysis and Wilcoxon rank‐sum tests. Results Tracheal mucociliary clearance rate was significantly decreased after transportation in both treatment (P = .002) and placebo (P = .03) groups. There was a significant effect of treatment on TMCR, with the treatment group showing half the reduction in TMCR compared with the placebo group (P = .002). Other significant differences between before‐ and after‐transportation samples occurred for serum fibrinogen, peripheral eosinophil count, quantitative culture, tracheal bacteria, and degenerate neutrophils, though no treatment effect was found. Conclusions and Clinical Importance Treatment with clenbuterol modestly attenuates the deleterious effects of this long‐distance transportation model on tracheal mucociliary clearance.